Lithostratigraphic comparison of three Diamictite successions of Nepal Lesser Himalaya - Dhital, M. R. (Journal of Nepal Geological Society, 1992)
ABSTRACT The Proterozoic Blaini-type of diamictite sequences have been identified from the Lesser Himalaya (Brookfield, 1987). A tillitic sequence called the Sisne Formation of Gondwana age was reported by Sakai (1983) from Tansen, the Western Nepal Lesser Himalaya. The newly reported Kokaha Diamictite and Sallyan Diamictite situated to the east and west of Tansen, respectively, exhibit some lithostratigraphic similarity with the Sisne Formation, though the underlying and overlying rocks are quite different The Kokaha Diamictite from the Barahakshetra area of Eastern Nepal is underlain by grey quartzite with coal seams and conglomerate lenses. Sometimes tuffs and agglomerates are also found together with the diamictite in some places. It is followed upsection by grey calcareous sandstone, siltstone and shale. The Sisne Formation from the Tansen area of Western Nepal overlies grey dolomite with a disconformity and is followed by the Taltung Formation separated by another disconformity. The Taltung Formation itself is composed of basic volcanics, conglomerate, sandstone and siltstone. A non-Blaini type of diamictite horizon called the Sallyan Diamictite from the Sallyan area of West Nepal occurs in low -grade metamorphic rocks. It disconformably overlies quartzite, meta-conglomerates and phyllites, and is transitionally followed by black carbonaceou s slates. Lack of reliable fossils, metamorphism and strong deformation pose difficulties in correlating it with other diamictites.